The Synergetic Effect of Multinational Corporation Management's Social Cognitive Capability on Tacit-Knowledge Management: Product Innovation Ability Insights from Asia. Issue 2 (June 2015) - Sheng, Margaret L.; Hartmann, Nathaniel N.; Chen, Qimei; Chen, Irene
Multinational corporations (MNCs) use their overseas subsidiaries to access tacit knowledge about host countries. It is generally assumed that subsidiary tacit knowledge contributes directly to greater product innovativeness; however, little empirical evidence supports this assumption. In this research, the authors propose a negative direct relationship between subsidiary tacit-knowledge level and MNCs' product innovation ability. The authors then examine the role of social cognitive capability as an attenuator of this negative relationship between subsidiary tacit-knowledge level and MNCs' product innovation ability. The results reveal that each of the MNCs' social cognitive capability components (i.e., task efficacy, organic structure, and affective trust) independently weakens this negative relationship. Moreover, combining social cognitive capabilities exerts synergetic influences to further excavate the effect of tacit knowledge.